One-dimensional Ni 12 Preparation method of P5 / Ni2P polycrystalline heterostructure high-efficiency water oxidation catalyst

By preparing one-dimensional Ni12P5/Ni2P polycrystalline heterostructure on commercial foam nickel, the problem of insufficient electrocatalytic performance of non-precious metal OER catalysts is solved, and the electrocatalytic water oxidation effect with low overpotential and high stability is achieved. It is suitable for electrocatalytic water oxidation reaction in alkaline electrolytes.

CN115261917BActive Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210775701.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-01
Publication Date
2025-04-11
Estimated Expiration
2042-07-01

AI Technical Summary

Technical Problem

The electrocatalytic performance of existing non-precious metal OER catalysts cannot meet the requirements of industrial applications, and there are problems such as poor conductivity, small specific surface area, and unstable catalysts, especially in alkaline electrolytic water systems.

Method used

A one-dimensional Ni12P5/Ni2P polycrystalline heterostructure was prepared on commercial nickel foam using a two-step hydrothermal-phosphorization method. By adjusting the electronic structure of Ni and P ions, a tightly bound polycrystalline heterostructure was formed to improve electrocatalytic activity and stability.

Benefits of technology

The OER electrocatalytic performance with low overpotential and long-term stability is achieved, which is better than the existing RuO2 catalysts, exhibits lower electrocatalytic water oxidation overpotential and high stability, and is suitable for electrocatalytic water oxidation reaction in alkaline electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003726991190000011
    Figure HDA0003726991190000011
  • Figure HDA0003726991190000012
    Figure HDA0003726991190000012
  • Figure HDA0003726991190000013
    Figure HDA0003726991190000013
Patent Text Reader

Abstract

The invention discloses a one-dimensional Ni 12 P 5 / Ni 2 A method for preparing a highly efficient water oxidation catalyst with a polycrystalline heterostructure is disclosed, wherein nickel foam is used as a conductive carrier and a nickel source, sodium phosphite is used as a phosphorus source, and a one-dimensional polycrystalline heterostructure catalyst Ni is synthesized by a two-step hydrothermal-phosphating method. 12 P 5 / Ni 2 P / NF. The polycrystalline heterostructure and interface effectively solve the problems of large overpotential, poor internal charge transfer, unstable catalyst and easy peeling of transition metal phosphides (TMPs) catalysts; the close combination of one-dimensional heterostructure and nickel foam conductive carrier is conducive to charge transfer and the release of bubbles on the electrode / electrolyte surface. 12 P 5 / Ni 2 The P / NF catalyst has a low electrocatalytic water oxidation overpotential and long-term stability in alkaline solution. 12 P 5 / Ni 2 Loading single-atom Ir on P / NF can further reduce the water oxidation overpotential, which has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and more particularly to one-dimensional Ni 12 P 5 / Ni 2 A method for preparing a highly efficient water oxidation catalyst with a polycrystalline heterostructure. Background Art

[0002] The huge development of the global economy and human society is highly dependent on fossil fuels, which is bound to lead to increasingly serious energy crises and environmental problems. In order to solve these problems, people have conducted a lot of research in the field of producing renewable hydrogen energy in electrochemical systems such as electrolytes, rechargeable metal-air batteries, fuel cells, and water electrolysis. However, the electrochemical performance of the above systems in producing renewable hydrogen is greatly restricted by the oxygen evolution reaction (OER). This is because in the OER process, multiple reaction intermediates produce slow OER kinetics, resulting in large overpotentials and significant energy efficiency losses. Therefore, people have conducted a lot of research to prepare highly active, highly stable and low-cost OER catalysts. Although the electrocatalysts based on precious metals have excellent water electrolysis performance, their content is scarce and their stability is low in alkaline water electrolysis systems, making them not ideal commercial catalysts.

[0003] In recent years, the development of metal-free, single-atom-dispersed, transition-metal-based OER electrocatalysts such as chalcogenides, borides, carbides, nitrides and phosphides with high activity, good stability and low cost has become the research focus of scientists. However, the electrocatalytic performance of such non-precious metal OER catalysts is far from meeting the requirements of industrial applications. At the same time, their poor conductivity and small specific surface area greatly hinder the charge transport inside the catalyst material and the contact between the electrolyte and the active sites on the catalyst surface. Among the many materials mentioned above, transition metal phosphides (TMPs) are considered to be one of the most promising electrocatalysts due to their high conductivity and easily adjustable electronic structure. However, the high ionic characteristics of positive metal (M = Co, Ni, Fe, etc.) atoms and highly electronegative non-metallic P atoms in TMPs weaken the electron delocalization ability, resulting in low electrocatalytic activity and poor stability. It is well known that one-dimensional nanomaterials have high electrochemically active specific surface area, fast charging and efficient transport of reactive species, and have broad application prospects in reducing overpotential. In addition, studies have shown that the nanorod structure can not only promote interfacial electron transfer by improving the electron transfer on the substrate surface, but also its structural characteristics are conducive to the release of bubbles on the electrode / electrolyte surface. Recently, strategies such as element doping, oxygen or phosphorus vacancies, crystal plane engineering and interface engineering have been widely used in the preparation of high-performance one-dimensional electrocatalytic materials. Among them, interface engineering has become one of the most effective strategies to improve the electrocatalytic activity and stability of water splitting. Although some progress has been made in the research of transition metal phosphide water splitting electrocatalysts, there is still a lack of TMPs-based electrocatalytic systems with low overpotential, high stability and long life. It should be pointed out that one-dimensional materials not only have good catalytic properties, but also can be used as effective support materials for electrocatalysis. It can be seen that the preparation of transition metal phosphide materials with one-dimensional unique polycrystalline heterostructure on nickel foam support is an effective way to obtain OER electrocatalysts with good activity and high stability. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a one-dimensional Ni 12 P 5 / Ni 2 The invention mainly uses low-priced commercial nickel foam (NF) as a conductive carrier and nickel source to obtain a one-dimensional Ni P polycrystalline heterostructure high-efficiency water oxidation catalyst through a two-step hydrothermal-phosphating method. 12 P 5 / Ni 2 P / NF polycrystalline heterostructure. The two-step hydrothermal method increases the roughness and defect level of nickel foam surface. Ni 12 P 5 / Ni 2The heterogeneous structure and interface in the P / NF catalyst cleverly regulate the electronic structure of Ni and P ions in the electrocatalyst, which is beneficial to reduce the energy barrier of the rate-limiting step. In addition, the one-dimensional polycrystalline heterostructure is conducive to the adsorption of water molecules on the catalytic site and the desorption of oxygen from the catalyst surface. In addition, the close connection between the polycrystalline heterojunction electrocatalyst and the nickel foam support effectively prevents the stripping of the catalyst during the reaction, thereby achieving a long-term stable effect in the alkaline electrolyte.

[0005] The technical means adopted by the present invention are as follows: a one-dimensional Ni 12 P 5 / Ni 2 A method for preparing a highly efficient water oxidation catalyst with a polycrystalline heterostructure is proposed. A low-cost commercial nickel foam (NF) is used as a conductive carrier and nickel source, and phosphite is used as a phosphorus source. A one-dimensional Ni 12 P 5 / Ni 2 P / NF polycrystalline heterostructure.

[0006] The phosphite is NaH 2 PO 2 ·H 2 O.

[0007] The preparation method specifically comprises the following steps:

[0008] 1. Cut nickel foam (NF) into a specific size, press it lightly to make it thinner, put it into 1.0-4.0M HCl solution for ultrasonic treatment for 20-60min, then ultrasonically treat it in deionized water, ethanol and acetone for 20-40min in sequence, put the washed nickel foam into a vacuum drying oven at 50-70℃ for 24-36h to obtain a clean NF sheet for standby use;

[0009] 2. Configuration (NH 4 ) 2 HPO 4 aqueous solution, placing the NF sheet obtained in step 1 therein for solvothermal reaction, the reaction temperature is controlled at 170-190°C, the time is controlled at 10-16h, naturally cooled to room temperature, washed with deionized water, vacuum dried in a vacuum drying oven at 50-70°C for 10-16h, the dried NF sheet is placed in a NaOH aqueous solution at 100-130°C for solvothermal reaction for 4-6h, washed and dried to obtain a nickel foam sheet r-NF with a rough surface and defects, which is set aside;

[0010] 3. NaH 2 PO 2 ·H 2O and the r-NF obtained in step 2 were mixed in different weight ratios and placed in a ceramic boat, and then placed together in a quartz tube. They were heated at 270-380°C for 2-4h in a tube furnace under a nitrogen atmosphere, cooled naturally to room temperature, washed and dried to obtain the target material Ni 12 P 5 / Ni 2 P / NF catalyst.

[0011] Based on the above scheme, preferably, in step 1, the size of the nickel foam is 3×3 to 6×6 cm 2 .

[0012] Based on the above scheme, preferably, in step 2, (NH 4 ) 2 HPO 4 The concentration of the aqueous solution is 1-2 mM, and the concentration of the NaOH aqueous solution is 100-200 mM.

[0013] Based on the above scheme, preferably, in step 3, NaH 2 PO 2 ·H 2 The weight ratio of O to the r-NF obtained in step 2 is 9 to 11:1.

[0014] Based on the above scheme, preferably, in step 3, the nitrogen flow rate is 100-150 sccm, the heating rate is 5-8°C / min, and the heating temperature is controlled at 270-380°C to obtain the material Ni 12 P 5 / Ni 2 P / NF-T, T is the heating temperature value, which can be 275℃, 300℃, 325℃, 350℃, and 375℃ respectively.

[0015] Based on the above scheme, preferably, in step 3, the nitrogen flow rate is 150sccm, the heating rate is 5°C / min, the heating temperature is controlled at 400°C, and the material Ni is obtained after natural cooling, washing and drying. 12 P 5 / NF.

[0016] Based on the above scheme, preferably, the nitrogen flow rate is 150sccm, the heating rate is 5°C / min, the heating temperature is controlled at 250°C, natural cooling, washing and drying are performed to obtain the material Ni 2 P / NF.

[0017] Based on the above scheme, preferably, in step 3, NaH 2 PO 2 ·H 2 O was placed upstream of the ceramic boat, the r-NF obtained in step 2 was placed downstream of the ceramic boat, and NaH 2 PO2 ·H 2 The weight ratio of O to r-NF was 9-11:1, the nitrogen flow rate was 150 sccm, the heating rate was 5°C / min, the heating temperature was controlled at 250°C, and the material Ni was obtained by natural cooling, washing and drying. 2 P / NF.

[0018] Based on the above scheme, preferably, in step three, the drying conditions are: vacuum drying at room temperature for 12-24 hours.

[0019] Based on the above scheme, preferably, the Ni prepared according to the above scheme 12 P 5 / Ni 2 P / NF catalyst, ethanol / water solution of potassium hexachloroiridate, drop the potassium hexachloroiridate solution onto the obtained Ni 12 P 5 / Ni 2 P / NF catalyst, then heated at 60-90℃, cooled naturally to room temperature to obtain Ir-Ni 12 P 5 / Ni 2 P / NF-275 catalyst;

[0020] Based on the above scheme, preferably, the concentration of potassium hexachloroiridate solution is 0.02-0.04 mM, and the solvent is a mixture of ethanol / water in a volume ratio of 1 / (1-2) to obtain Ir x -Ni 12 P 5 / Ni 2 Ir and Ni in P / NF-T materials 12 P 5 / Ni 2 The mass ratio of the P / NF catalyst is 0.01-0.04:1, and x=1-4, for example, 1, 2, 3 or 4.

[0021] In another aspect, the present invention provides an application of the above catalyst in electrocatalytic water separation and oxygen separation. The specific reaction conditions are: the obtained Ni 12 P 5 / Ni 2 P / NF-T、Ni 12 P 5 / NF、Ni 2 P / NF or Ir-Ni 12 P 5 / Ni 2 The P / NF catalyst is directly used as the oxygen evolution electrode to carry out the electrocatalytic water decomposition reaction in a two-electrode system.

[0022] Based on the above scheme, preferably, the electrolyte used in the electrocatalytic water decomposition reaction is an alkaline electrolyte, the base is one of KOH, NaOH, LiOH, and CsOH, preferably KOH; the concentration of the alkaline electrolyte is 0.5-10M, preferably 1M.

[0023] Beneficial effects of the present invention: The one-dimensional Ni 12 P 5 / Ni 2 The raw materials used in the P polycrystalline heterostructure efficient water oxidation catalyst are low in price, the synthesis method is simple and convenient, the chemical properties are stable, the electrode structure is robust, it has excellent OER activity and stability, and it is easy to promote and apply. Using nickel foam as a conductive carrier and nickel source, a one-dimensional polycrystalline heterostructure catalyst is synthesized by a two-step hydrothermal-phosphating method, which can effectively solve the problems of large overpotential, poor internal charge transfer, unstable catalyst and easy peeling of TMPs catalyst in the prior art. In addition, the one-dimensional heterostructure is tightly combined with the conductive carrier nickel foam, which is beneficial to charge transfer and the release of bubbles on the electrode / electrolyte surface. The prepared Ni 12 P 5 / Ni 2 The P / NF catalyst performs electrocatalytic water oxidation in alkaline solution and has a low electrocatalytic water oxidation overpotential and long-term stability, 10 mA / cm 2 The overpotential at this current density is 254 mV, which is better than the current best RuO 2 Catalyst (overpotential 295mV), corresponding Ni 2 P / NF (overpotential 278mV) and Ni 12 P 5 / NF (overpotential is 288mV); at 50mA / cm 2 The stability of Ir single atoms loaded on Ni 12 P 5 / Ni 2 When the P / NF polycrystalline heterostructure is formed, the water oxidation overpotential can be further reduced to 10 mA / cm 2 The overpotential can be further reduced to 196 mV at a current density of 50 mA / cm 2 Stability for more than 100 h at a current density of 1.5 Å. This two-step hydrothermal and phosphating method using commercial nickel foam as a precursor shows broad application prospects in the synthesis of alkaline OER electrocatalysts.

[0024] Based on the above reasons, the present invention can be widely promoted in the fields of water decomposition electrocatalytic materials and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The target material is Ni12 P 5 / Ni 2 Transmission electron microscopy (TEM) image of P / NF-275.

[0026] Figure 2 The target material is Ni 12 P 5 / Ni 2 High-resolution transmission electron microscopy (HRTEM) image of P / NF-275.

[0027] Figure 3 The target material is Ni 12 P 5 / Ni 2 P / NF-275、Ni 12 P 5 / NF、Ni 2 P / NF and RuO 2 LSV polarization curves of / NF.

[0028] Figure 4 The target material is Ni 12 P 5 / Ni 2 P / NF-275 at 50mA / cm -2 Stability test diagram under current density (test time 200h).

[0029] Figure 5 Target material 3% Ir-Ni 12 P 5 / Ni 2 Spherical aberration transmission electron microscopy (HAADF-STEM) image of P / NF-275.

[0030] Figure 6 For target material x% Ir-Ni 12 P 5 / Ni 2 LSV polarization curve of P / NF-275.

[0031] Figure 7 Target material 3% Ir-Ni 12 P 5 / Ni 2 P / NF-275 at 50mA / cm -2 Stability test diagram under current density (test time 120h). DETAILED DESCRIPTION

[0032] In order to further illustrate the present invention, the following embodiments are listed and described in detail with reference to the accompanying drawings, but they do not limit the scope of the invention defined by the appended claims.

[0033] Example 1

[0034] Cut the nickel foam (NF) into 3×3cm 2 , press lightly to make it thinner, put it into 3.0M HCl solution for ultrasonic treatment for 30 minutes, then ultrasonically treat it in deionized water, ethanol and acetone for 30 minutes in sequence, put the washed nickel foam into a vacuum drying oven at 60℃ for 24 hours to obtain a clean NF sheet for use.

[0035] Prepare 1mM (NH 4 ) 2 HPO 4 aqueous solution, put the NF sheet obtained in step 1 into it, carry out solvent thermal reaction, control the reaction temperature to 160 ° C, control the time to 12h, naturally cool to room temperature, wash with deionized water, and vacuum dry in a vacuum drying oven at 60 ° C for 12h. Put the dried NF sheet into 100mM NaOH aqueous solution at 120 ° C for solvent thermal reaction for 5h, wash with deionized water, and then put it into a vacuum drying oven to dry overnight at room temperature to obtain a foam nickel sheet r-NF with a rough surface and defects, which is set aside.

[0036] NaH 2 PO 2 ·H 2 O and the r-NF obtained in step 2 were mixed in a weight ratio of 10:1 and placed in a ceramic boat, and then placed together in a quartz tube, heated at 275°C for 2h in a tube furnace under a nitrogen atmosphere (nitrogen flow rate of 150sccm, heating rate of 5°C / min), cooled naturally to room temperature, washed with deionized water, and then placed in a vacuum drying oven to dry overnight at room temperature to obtain the target material Ni 12 P 5 / Ni 2 P / NF-275.

[0037] Structural characterization of target materials: transmission electron microscopy ( Figure 1 ) and high-resolution transmission electron microscopy images ( Figure 2 ) It can be seen that the target material is a polycrystalline heterostructure, and the lattice fringe spacing of 0.192nm corresponds to Ni 2 The (210) crystal plane of P, 0.195nm and 0.22nm correspond to Ni 12 P 5 (420) and (202) crystal planes.

[0038] Ni 12 P 5 / Ni 2Electrochemical testing of P / NF-275 catalyst: The electrochemical performance of the target material was tested on an electrochemical workstation, using a graphite rod as the counter electrode and a Hg / HgO electrode (KOH, 1 M) as the reference electrode. According to the Nernst equation, all potentials measured in this paper were calibrated to the reversible hydrogen electrode (RHE), E(RHE) = 0.098 + E(Hg / HgO) + 0.0592 × pH. 2 Polarization curves were recorded at a scan rate of 1 mV / s in a saturated 1 M KOH electrolyte. Both the polarization curves and the Tafel slopes were iR compensated by 90%. The electrochemical double layer capacitance was measured by cyclic voltammetry (CV) at different scan rates in the potential range of 0.9 V to 1.02 V (vs. Hg / HgO). The EIS test recorded data in the range of 0.1 Hz to 100 kHz at a potential of 1.53 V (vs. RHE). Stability test conditions: Chronoamperometry, I = 50 mA / cm 2 The obtained polarization curves, double layer capacitance diagrams, EIS and stability tests are as follows: Figures 3-4 As shown. Polarization curve ( Figure 3 ) It can be seen that at 10mA / cm 2 The corresponding overpotential under current density is 254mV, which is better than similar materials Ni 12 P 5 / NF、Ni 2 P / NF and commercial RuO 2 / NF; at 50mA / cm 2 The corresponding overpotential under current density is 295mV. The stability test results show that the catalyst 2 The performance was stable during the 200h test period under the current density ( Figure 4 ).

[0039] Example 2

[0040] The preparation and processing of r-NF were the same as in Example 1.

[0041] NaH 2 PO 2 ·H 2 O and the r-NF obtained in step 2 were mixed in a weight ratio of 10:1 and placed in a ceramic boat, and then placed in a quartz tube together. They were heated at 300°C for 2h in a tube furnace under a nitrogen atmosphere (nitrogen flow rate was 150cc, and the heating rate was 5°C / min), cooled naturally, washed with deionized water, and then placed in a vacuum drying oven to dry overnight at room temperature to obtain the target material Ni 12 P 5 / Ni 2 P / NF-300.

[0042] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 3 , at 50mA / cm 2 The corresponding overpotential under current density conditions is 324mV.

[0043] Example 3

[0044] The preparation and processing of r-NF were the same as in Example 1.

[0045] NaH 2 PO 2 ·H 2 O and the r-NF obtained in step 2 were mixed in a weight ratio of 10:1 and placed in a ceramic boat, and then placed in a quartz tube together. They were heated at 325°C for 2h in a tube furnace under a nitrogen atmosphere (nitrogen flow rate was 150cc, and the heating rate was 5°C / min), cooled naturally, washed with deionized water, and then placed in a vacuum drying oven to dry overnight at room temperature to obtain the target material Ni 12 P 5 / Ni 2 P / NF-325.

[0046] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 3 , at 50mA / cm 2 The corresponding overpotential under current density conditions is 330mV.

[0047] Example 4

[0048] The preparation and processing of r-NF were the same as in Example 1.

[0049] NaH 2 PO 2 ·H 2 O and the r-NF obtained in step 2 were mixed in a weight ratio of 10:1 and placed in a ceramic boat, and then placed in a quartz tube together. They were heated at 350°C for 2h in a tube furnace under a nitrogen atmosphere (nitrogen flow rate was 150sccm, and the heating rate was 5°C / min), cooled naturally, washed with deionized water, and then placed in a vacuum drying oven to dry overnight at room temperature to obtain the target material Ni 12 P 5 / Ni 2 P / NF-350.

[0050] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 3 , at 50mA / cm 2 The corresponding overpotential under current density conditions is 340mV.

[0051] Example 5

[0052] The preparation and processing of r-NF were the same as in Example 1.

[0053] NaH2 PO 2 ·H 2 O and the r-NF obtained in step 2 were mixed in a weight ratio of 10:1 and placed in a ceramic boat, and then placed in a quartz tube together. They were heated at 375°C for 2h in a tube furnace under a nitrogen atmosphere (nitrogen flow rate was 150cc, and the heating rate was 5°C / min), cooled naturally to room temperature, washed with deionized water, and then placed in a vacuum drying oven to dry overnight at room temperature to obtain the target material Ni 12 P 5 / Ni 2 P / NF-375.

[0054] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 3 , at 50mA / cm 2 The corresponding overpotential under current density conditions is 351mV.

[0055] Example 6

[0056] Prepare an ethanol / water solution of potassium hexachloroiridate with a concentration of 0.02 mM (volume ratio 1 / 1), and drop 100 μL of the potassium hexachloroiridate solution onto the Ni prepared in Example 1. 12 P 5 / Ni 2 The target 1% Ir-Ni was obtained by heating at 70 °C for 2 h and cooling to room temperature. 12 P 5 / Ni 2 P / NF-275 catalyst.

[0057] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 6 , at 10mA / cm 2 The corresponding overpotential under current density conditions is 230mV; 50mA / cm 2 The corresponding overpotential under current density conditions is 274mV.

[0058] Example 7

[0059] Prepare an ethanol / water solution of potassium hexachloroiridate with a concentration of 0.02 mM (volume ratio 1 / 1), and drop 200 μL of the potassium hexachloroiridate solution onto the Ni prepared in Example 1. 12 P 5 / Ni 2 The target 2% Ir-Ni was obtained by heating at 70 °C for 2 h and cooling to room temperature. 12 P 5 / Ni 2 P / NF-275 catalyst.

[0060] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 6 , at 10mA / cm 2 The corresponding overpotential under current density conditions is 210mV; 50mA / cm 2 The corresponding overpotential under current density conditions is 258mV.

[0061] Example 8

[0062] Prepare an ethanol / water solution of potassium hexachloroiridate with a concentration of 0.02 mM (volume ratio 1 / 1), and drop 300 μL of the potassium hexachloroiridate solution onto the Ni prepared in Example 1. 12 P 5 / Ni 2 The target 3% Ir-Ni was obtained by heating at 70 °C for 2 h and cooling to room temperature. 12 P 5 / Ni 2 P / NF-275 catalyst.

[0063] Target material 3% Ir-Ni 12 P 5 / Ni 2 P / NF-275 is a one-dimensional polycrystalline heterostructure. Spherical aberration electron microscopy ( Figure 5 ) It can be seen that Ir in Ni 12 P 5 / Ni 2 P / NF-275 is a single atom dispersion.

[0064] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 6 , at 10mA / cm 2 The corresponding overpotential under current density conditions is 199mV; 50mA / cm 2 The corresponding overpotential under the current density condition is 239mV. The stability test results show that the catalyst 2 The performance was stable during the 120h test period under the current density ( Figure 7 ).

[0065] Example 9

[0066] Prepare an ethanol / water solution of potassium hexachloroiridate with a concentration of 0.02 mM (volume ratio 1 / 1), and drop 400 μL of the potassium hexachloroiridate solution onto the Ni prepared in Example 1. 12 P 5 / Ni 2 The target 4% Ir-Ni was obtained by heating at 70 °C for 2 h and cooling to room temperature. 12 P 5 / Ni2 P / NF-275 catalyst.

[0067] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 6 , at 10mA / cm 2 The corresponding overpotential under current density conditions is 200mV; 50mA / cm 2 The corresponding overpotential under current density conditions is 240mV.

[0068] Comparative Example 1

[0069] Non-heterostructure Ni 12 P 5 Control experiment of electrochemical water oxidation of / NF catalyst.

[0070] The preparation and processing of r-NF were the same as in Example 1.

[0071] NaH 2 PO 2 ·H 2 O and the r-NF obtained in step 2 were mixed in a weight ratio of 10:1 and placed in a ceramic boat. They were then placed in a quartz tube and heated at 400°C for 2 h in a tube furnace under a nitrogen atmosphere (nitrogen flow rate of 150 sccm and heating rate of 5°C / min). The mixture was cooled naturally, washed and dried to obtain the target material Ni 12 P 5 / NF.

[0072] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 3 , at 10mA / cm 2 The corresponding overpotential under current density conditions is 288mV; 50mA / cm 2 The corresponding overpotential under current density conditions is 358mV.

[0073] Comparative Example 2

[0074] Non-heterostructure Ni 2 Control experiment of electrochemical water oxidation of P / NF catalyst.

[0075] The preparation and processing of r-NF were the same as in Example 1.

[0076] NaH 2 PO 2 ·H 2 O was placed upstream of the ceramic boat, r-NF was placed downstream of the ceramic boat, and NaH 2 PO 2 ·H 2The weight ratio of O to r-NF was 10:1, the nitrogen flow rate was 150 sccm, the heating rate was 5 °C / min, the heating temperature was controlled at 250 °C, and the material Ni was obtained after natural cooling, washing and drying. 2 P / NF.

[0077] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 3 , at 10mA / cm 2 The corresponding overpotential under current density conditions is 278mV; 50mA / cm 2 The corresponding overpotential under current density conditions is 320mV.

[0078] Comparative Example 3

[0079] Commercial RuO 2 Control experiment of electrochemical water oxidation supported on nickel foam.

[0080] 5 mg of commercial RuO 2 The catalyst was dispersed in 450 μL of a water / ethanol mixed solvent with a volume ratio of 1:3.5, and 50 μL of a 5% Nafion aqueous solution was added thereto. Ultrasound was continued for 30 min to form a uniform ink-like mixed solution. Then, the prepared catalyst ink-like mixed solution was dropped on a 0.5×0.5 cm 2 On the nickel foam (content is about 1.0mg / cm 2 ) as the working electrode.

[0081] The electrochemical test conditions are the same as those in Example 1, and the electrochemical test performance is shown in Figure 3 , at 10mA / cm 2 The corresponding overpotential under current density conditions is 294mV; 50mA / cm 2 The corresponding overpotential under current density conditions is 373mV.

Claims

1. A one-dimensional Ni 12 The preparation method of a P5 / Ni2P polycrystalline heterostructure high-efficiency water oxidation catalyst is characterized in that: The preparation method comprises the following steps:

1. The nickel foam is placed in a 1.0-4.0M HCl solution and ultrasonically treated for 20-60 min, and then ultrasonically treated in deionized water, ethanol, and acetone for 20-40 min in sequence, and the washed nickel foam is dried to obtain a clean nickel foam sheet for standby use; 2. Place the nickel foam obtained in step 1 into a (NH4)2HPO4 aqueous solution for solvent thermal reaction, control the reaction temperature at 170-190°C for 10-16h, cool naturally to room temperature, wash, and dry for 12h. Place the dried nickel foam in a NaOH aqueous solution for solvent thermal reaction at 100-130°C for 4-6h, wash, and dry to obtain a nickel foam with rough surface and defects for standby use.

3. Mix NaH2PO2·H2O with the rough and defective nickel foam sheet obtained in step 2, heat it at 270-380°C in a tube furnace under a nitrogen atmosphere for 2-3h, cool it naturally, wash it, and dry it to obtain Ni 12 P5 / Ni2P / NF catalyst.

2. The preparation method according to claim 1, characterized in that: In step 1, the size of the nickel foam is 3×3~6×6cm 2 ; Drying conditions: 50-70℃ vacuum drying for 24-36h.

3. The preparation method according to claim 1, characterized in that: In step 2, the concentration of the (NH4)2HPO4 aqueous solution is 1-2 mM, and the concentration of the NaOH aqueous solution is 100-200 mM; the drying conditions are: vacuum drying at 50-70°C for 10-16 hours.

4. The preparation method according to claim 1, characterized in that: In step 3, the weight ratio of NaH2PO2·H2O to the nickel foam sheet with rough surface and defects obtained in step 2 is 9-11:

1.

5. The preparation method according to claim 1, characterized in that: In step three, the nitrogen flow rate is 100-150 sccm, and the heating rate is controlled at 5-8°C / min; the drying conditions are: vacuum drying at room temperature for 12-24 hours.

6. A one-dimensional Ir-Ni 12 The preparation method of a P5 / Ni2P / NF polycrystalline heterostructure high-efficiency water oxidation catalyst is characterized in that: The preparation method comprises the following steps:

1. The nickel foam is placed in a 1.0-4.0M HCl solution and ultrasonically treated for 20-60 min, and then ultrasonically treated in deionized water, ethanol, and acetone for 20-40 min in sequence, and the washed nickel foam is dried to obtain a clean nickel foam sheet for standby use; 2. Place the nickel foam obtained in step 1 into a (NH4)2HPO4 aqueous solution for solvent thermal reaction, control the reaction temperature at 170-190°C for 10-16h, cool naturally to room temperature, wash, and dry for 12h. Place the dried nickel foam in a NaOH aqueous solution for solvent thermal reaction at 100-130°C for 4-6h, wash, and dry to obtain a nickel foam with rough surface and defects for standby use.

3. Mix NaH2PO2·H2O with the rough and defective nickel foam sheet obtained in step 2, heat it at 270-380°C in a tube furnace under a nitrogen atmosphere for 2-3h, cool it naturally, wash it, and dry it to obtain Ni 12 P5 / Ni2P / NF catalyst; 4. Dissolve potassium hexachloroiridate in an ethanol / water mixed solvent with a volume ratio of 1:1-2 to prepare an ethanol / water solution of potassium hexachloroiridate, and drop the potassium hexachloroiridate solution onto the obtained Ni 12 P5 / Ni2P / NF catalyst, then heated at 60-90℃ for 2-4h, and naturally cooled to obtain Ir-Ni 12 P5 / Ni2P / NF catalyst.

7. The preparation method according to claim 6, characterized in that: In step 1, the size of the nickel foam is 3×3~6×6cm 2 ; Drying conditions: 50-70℃ vacuum drying for 24-36h.

8. The preparation method according to claim 6, characterized in that: In step 2, the concentration of the (NH4)2HPO4 aqueous solution is 1-2 mM, and the concentration of the NaOH aqueous solution is 100-200 mM; the drying conditions are: vacuum drying at 50-70°C for 10-16 hours.

9. The preparation method according to claim 6, characterized in that: In step 3, the weight ratio of NaH2PO2·H2O to the nickel foam sheet with rough surface and defects obtained in step 2 is 9-11:

1.

10. The preparation method according to claim 6, characterized in that: In step three, the nitrogen flow rate is 100-150 sccm, and the heating rate is controlled at 5-8°C / min; the drying conditions are: vacuum drying at room temperature for 12-24 hours.

11. The preparation method according to claim 6, characterized in that: The concentration of potassium hexachloroiridate solution is 0.02-0.04mM to obtain Ir-Ni 12 Ir and Ni in P5 / Ni2P / NF catalyst 12 The mass ratio of P5 / Ni2P / NF catalyst is 0.01-0.04:

1.

12. A method for preparing Ni according to any one of claims 1 to 5 12 Application of P5 / Ni2P / NF catalyst in electrocatalytic oxygen production.

13. A method for preparing Ir-Ni according to any one of claims 6 to 11 12 Application of P5 / Ni2P / NF catalyst in electrocatalytic oxygen production.

14. The use according to any one of claims 12 to 13, characterized in that: The electrolyte used in the electrocatalytic water decomposition reaction is an alkaline electrolyte, and the alkali is one of KOH, NaOH, LiOH, and CsOH; the concentration of the alkaline electrolyte is 0.5-10M.

Citation Information

Patent Citations

  • Full-water-electrolysis catalyst, and preparation method and application thereof

    CN110639566A

  • Heterogeneous nickel phosphide material and preparation method thereof

    CN114164448A